Making sense of mining history
1 online resource
Keywords: This book draws together international contributors to analyse a wide range of aspects of mining history across the globe including mining archaeology, technologies of mining, migration and mining, the everyday life of the miner, the state and mining, industrial relations in mining, gender and mining, environment and mining, mining accidents, the visual history of mining, and mining heritage. The result is a counter balance to more common national and regional case study perspectives.